2019
DOI: 10.1002/jcp.28225
|View full text |Cite
|
Sign up to set email alerts
|

Advanced strategies for combating bacterial biofilms

Abstract: Biofilms are communities of microorganisms that are formed on and attached to living or nonliving surfaces and are surrounded by an extracellular polymeric material. Biofilm formation enjoys several advantages over the pathogens in the colonization process of medical devices and patients' organs. Unlike planktonic cells, biofilms have high intrinsic resistance to antibiotics and sanitizers, and overcoming them is a significant problematic challenge in the medical and food industries. There are no approved trea… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
89
1

Year Published

2019
2019
2023
2023

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 104 publications
(90 citation statements)
references
References 209 publications
(312 reference statements)
0
89
1
Order By: Relevance
“…Comprehensive analysis of the multicomponent nature of the biofilm has chalked out few excellent targets for combating microbial infections and infectious diseases [ 1 , 8 , 9 ]. The biofilm inhibition approaches can be categorized into four classes: (i) targeting bacterial adhesion and EPS components, (ii) targeting biofilm metabolism, (iii) facilitating biofilm dispersal and (iv) targeting dormant cells [ 7 , 8 , 9 , 10 ]. The early stages of biofilm formation (i.e., bacterial adhesion and EPS synthesis) can be targeted using molecules such as bacterial adhesion inhibitors (mannoside derivatives), cyclic-di-GMP pathway targeting molecules (e.g., cephalosporin-3′-diazeniumdiolate) and inhibitors of lipopolysaccharide (LPS) synthesis enzymes (e.g., LpxC inhibitors) [ 7 , 8 , 9 , 10 ].…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations
“…Comprehensive analysis of the multicomponent nature of the biofilm has chalked out few excellent targets for combating microbial infections and infectious diseases [ 1 , 8 , 9 ]. The biofilm inhibition approaches can be categorized into four classes: (i) targeting bacterial adhesion and EPS components, (ii) targeting biofilm metabolism, (iii) facilitating biofilm dispersal and (iv) targeting dormant cells [ 7 , 8 , 9 , 10 ]. The early stages of biofilm formation (i.e., bacterial adhesion and EPS synthesis) can be targeted using molecules such as bacterial adhesion inhibitors (mannoside derivatives), cyclic-di-GMP pathway targeting molecules (e.g., cephalosporin-3′-diazeniumdiolate) and inhibitors of lipopolysaccharide (LPS) synthesis enzymes (e.g., LpxC inhibitors) [ 7 , 8 , 9 , 10 ].…”
Section: Introductionmentioning
confidence: 99%
“…The biofilm inhibition approaches can be categorized into four classes: (i) targeting bacterial adhesion and EPS components, (ii) targeting biofilm metabolism, (iii) facilitating biofilm dispersal and (iv) targeting dormant cells [ 7 , 8 , 9 , 10 ]. The early stages of biofilm formation (i.e., bacterial adhesion and EPS synthesis) can be targeted using molecules such as bacterial adhesion inhibitors (mannoside derivatives), cyclic-di-GMP pathway targeting molecules (e.g., cephalosporin-3′-diazeniumdiolate) and inhibitors of lipopolysaccharide (LPS) synthesis enzymes (e.g., LpxC inhibitors) [ 7 , 8 , 9 , 10 ]. Early biofilms and mature biofilms can be eradicated using structural protein inhibitors (e.g., ring-fused 2-pyridones), eDNA-targeting molecules (e.g., alginate derivatives), QS inhibitor peptides (e.g., AIP-I or RIP), EPS-degrading enzymes (e.g., glucanohydrolases or dispersin) and monoclonal antibodies (e.g., Ebp A) [ 7 , 8 , 9 , 10 ].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…1 Hardly are biofilms detectable with routine diagnostic tests; therefore, the management of their infections are challenging in the clinic. 2 Methicillinresistant Staphylococcus aureus (MRSA), Streptococcus mutans, Pseudomonas aeruginosa, S. epidermidis and Gardnerella vaginalis are the most common biofilm formers in the clinic. 3 Different strategies like new generations of antibiotics and the inhibition of biofilm formation by quorum sensing (QS) inhibitors have been developed.…”
Section: Introductionmentioning
confidence: 99%
“…Longitudinal studies that follow the progression of P. aeruginosa strains from early colonization through chronic infection have shown that the bacteria quickly evolve and adapt to the conditions found in the CF lung, and that many of the genetic changes seen in chronic P. aeruginosa strains function to decrease overall bacterial pathogenicity [32][33][34] . For example, mucA mutations, which downregulate the expression of virulence-associated type III secretion systems, are frequently observed 35,36 . Additionally, researchers have found mutations that decrease quorum sensing and, notably for this discussion, biofilm formation 32,33 .…”
Section: Discussionmentioning
confidence: 99%